Interactive web development to showcase the green space and associated social and wellbeing indicator - Heng, Zheng Ping (Nanyang Technological University, 2023)
In Singapore, due to limited land space and dense population, residential buildings are often positioned along busy roads. As a result, extended exposure to noise leads to health problems such as high blood pressure. Besides man-made noise barriers, studies have shown that trees conveniently serve as a practical alternative for noise absorption and offer various additional advantages.